7(x-4)+2=4x+3(x+9)

Simple and best practice solution for 7(x-4)+2=4x+3(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-4)+2=4x+3(x+9) equation:


Simplifying
7(x + -4) + 2 = 4x + 3(x + 9)

Reorder the terms:
7(-4 + x) + 2 = 4x + 3(x + 9)
(-4 * 7 + x * 7) + 2 = 4x + 3(x + 9)
(-28 + 7x) + 2 = 4x + 3(x + 9)

Reorder the terms:
-28 + 2 + 7x = 4x + 3(x + 9)

Combine like terms: -28 + 2 = -26
-26 + 7x = 4x + 3(x + 9)

Reorder the terms:
-26 + 7x = 4x + 3(9 + x)
-26 + 7x = 4x + (9 * 3 + x * 3)
-26 + 7x = 4x + (27 + 3x)

Reorder the terms:
-26 + 7x = 27 + 4x + 3x

Combine like terms: 4x + 3x = 7x
-26 + 7x = 27 + 7x

Add '-7x' to each side of the equation.
-26 + 7x + -7x = 27 + 7x + -7x

Combine like terms: 7x + -7x = 0
-26 + 0 = 27 + 7x + -7x
-26 = 27 + 7x + -7x

Combine like terms: 7x + -7x = 0
-26 = 27 + 0
-26 = 27

Solving
-26 = 27

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3x+4(1.5)=6 | | 9x+8+2x-7=18 | | (7-x)(6-x)=0 | | 9x-20+10x-5=3x-6x-15 | | .24g+14.8=16.24 | | F(x)=2x^2+7x-12 | | -9g=-9g+8 | | 3x+40=2x+20 | | 1/3(x-9)1/8(3x-1) | | 4x^2-36x+72= | | 13i+7=2i-9 | | 594=18b+72 | | 2(x+2)=6x+1-4x+3 | | -6w+10=-10-8w | | x(5)=315 | | 2z+4z+2+z+10=z+2+20 | | 9y+5=15y+7 | | s^3+2s^2+12s-40=0 | | 120-80y=-3y+9 | | 4+4y+2=-2 | | 46/n=117 | | N^2-12n=32 | | 4a(5)3= | | 2x-5=2x+18 | | m-11=15-6b | | -6x+-6x= | | t=1.25h-10 | | -1-7x=36x+(-7-x) | | -6z+6=6-6z | | 0.2v=1.2 | | 2(y-1)+6y=10 | | 25-6x=-65 |

Equations solver categories